Accounting for Yolŋu ranger work in the Dhimurru Indigenous Protected Area, Australia - Margaret L. Ayre (Resilience Alliance, 2021)
Over the past decade, there has been increased international interest in understanding and recognizing the contribution of Indigenous natural and cultural resource management, including Indigenous ranger work, to the sustainable management of social-ecological systems. In Australia, Indigenous rangers are responsible for managing land and seas that represent approximately 44% of the national protected area estate. Governments and other coinvestors seek to evaluate this ranger work and its contribution to biodiversity conservation and other public goods. However, current monitoring and evaluation approaches are based in conceptions of value and benefits and do not capture the full range of contributions and meanings associated with this work. We present an empirical case study from northern Australia in which we explore how to properly account for the full complexity and richness of Indigenous ranger work. We demonstrate that the work of being an Indigenous ranger at a Yolŋu (Indigenous people of Northeast Arnhem Land) land and sea management organization, (the Dhimurru Aboriginal Corporation or Dhimurru), can be understood as three sets of knowledge practices: the practices of "knowing and being known by Yolŋu country;" the practices of "mobilizing the Dhimurru Vision Statement;" and, the practices of "being ralpa" (Ralpa is a Yolŋu concept that means being willing to work and prepared to take on leadership responsibilities.) We contend that these knowledge practices represent criteria for judging the effectiveness of Yolŋu ranger work. The Dhimurru knowledge community of senior Yolŋu landowners and their collaborators, judge the effectiveness of Yolŋu ranger work based on whether Yolŋu rangers demonstrate these practices. By integrating such criteria into Dhimurru's formal monitoring and evaluation processes endorsed by its government funding partners, Dhimurru can more effectively and fully demonstrate the contribution of Yolŋu rangers to the Yolŋu vision for ecologically and culturally sustainable management of the Dhimurru Indigenous Protected Area in the Northern Territory as part of Australia's national conservation estate.